Study of Energy Saving Potential in Tun Fatimah Residential College (KKTF) Three Residential Building by Using Energyplus Software - Arif Hakimi Norzaki; Azian Hariri (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Since Malaysia's growing demand for electric energy, this study examines how energy is used in residential buildings at Universiti Tun Hussein Onn Malaysia (UTHM)'s Tun Fatimah Residential College (KKTF). EnergyPlus and OpenStudio are two examples of simulation tools that will be used in the project to design and evaluate energy models of individual buildings with an emphasis on possible energy savings. Data gathering, energy-saving scenario simulations, and validation against previous energy audits are all part of the protocols. Building orientation and window features have an impact on sunlight exposure, and the EnergyPlus simulations improved our understanding of the thermal conditions, solar exposure, and energy performance of KKTF buildings dramatically. Energy-saving measures including installing photovoltaic systems, overhanging structures, and energy-efficient LED lighting have been shown to be successful by identifying patterns in daily and annual energy consumption. It's noteworthy that rooftop solar systems cut usage by 37.98% annually and as much as 41.13% monthly. These results highlight the vital role that sustainable construction techniques play in helping Malaysia achieve its environmental goals. Specifically, they highlight the ways that deliberate architectural changes improve energy efficiency, lower costs, and advance sustainability in KKTF complexes.